Significance of timely reference on maternal morbidity and mortality - Chandrayan, Piyusha; Merawat, Rohit K.; Parekh, Usha P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The objective is to evaluate the effectiveness of the timely maternal referral system to a tertiary care centre in reducing maternal morbidity and mortality. Well known causes of maternal mortality are delays at three levels: in seeking care, in referring/reaching health facility in time and in receiving adequate treatment. In this study, authors have made an attempt to focus mainly on the referral system in improving maternal morbidity and mortality. Methods: This was an observational study, conducted at Dhiraj General Hospital, a rural tertiary health care facility, affiliated to SBKSMC and RC located in Waghodia district,16 kms away from the Vadodara city. It covers an area of around 7,550 sq kms of rural areas. All the patients referred from any centre and admitted to emergency obstetrical ward were included under the study within the study time period. Results: The total incidence of referred patients in this study accounted for 7.49%. 70% of the patients under study were unbooked. 65% of the referrals were multigravida. 35% of the patients were of age group 24-29 yrs. Hemorrhage, accounting 39% was the most common cause of referral. The bulk of referrals,70% were within the 50km circumference. 65% of present referred cases reached within 5 hours from the referring centre due to timely referral and easy accessibility of the transport system like - availability of 108. Conclusions: Timely referrals of women have significantly reduced the maternal morbidity and mortality as patients from remote area can avail tertiary medical health facilities. A proper referral letter with primary care from the referring centre can further enhance the functioning of this system.